ANALYSIS OF THE MOVEMENT ACTIVITIES OF PUPILS IN THE EVALUATION OF PHYSICAL EDUCATION AND SPORTS IN GENERAL SECONDARY SCHOOLS - Khanturaev, N.A. (SCIENCE and SOCIETY, 2021)
Physical education and sports in school curriculum are the decisive factor for the development of physical qualities as well as the provision of physical activity in young generation [1]. It is a noteworthy subject area for learning and engaging in, and helps pupils become competent movers, builds self-confidence and lays a foundation for participation in lifetime physical activity. Moreover, physical education and sport have the potential to make momentous contributions to the education and development of children in many ways. For the most children, school constitutes the natural environment for being physically active throughout the physical education and sport program. As the physical education and sport activities are well introduced, daily participation in such activities is associated with a better quality of life, can lessen the possibility of a variety of different diseases, and also plenty of psychological and emotional benefits [2]. Researchers have suggested that physical education and sport can enhance academic performance by increasing blood flow to the brain, enhancing mood, increasing mental alertness, and improving self-esteem. Since it is clear evidence that physical education and sport can have a positive impact on the psychological well-being of schoolchildren, this article covers movement and action activities that have a profound impact upon pupils’ health who enrol in general secondary schools.